Menu of happiness - Kashiwai, Hisashi (The kamogawa food detectives, 2025)
"Every memory has a flavor. A very special restaurant in Kyoto helps find them . . . Welcome to the Kamogawa Diner, where every meal is a mystery ready to be solved. This unique establishment is run by a father-daughter duo who offer more than just mouth-watering meals. They act as "food detectives," delving into the past to produce nostalgia-infused dishes for their hungry clientele. Among the patrons is a once-renowned pianist whose promising career was marred by a self-inflicted injury. She longs to taste the yakisoba shared with the only man she ever truly loved. The diner also welcomes a man haunted by shadows of regret. His mind is haunted by the memory of gyoza served by the parents of a lover he once jilted, as he seeks understanding and, perhaps, forgiveness. The Kamogawa Diner doesn't just serve food - it recreates forgotten recipes, helping its patrons to revisit memories lost to time. Each dish is a portal to the past, serving not just sustenance but solace and reconnection through the miracle of delicious food"--